PCBs in Chinstrap Penguins from Deception Island (South Shetland Islands, Antarctica) - Motas, Miguel; Jerez-Rodríguez, Silvia; Veiga-del-Baño, José Manuel; Ramos, Juan José; Oliva, José; Cámara, Miguel Ángel; Andreo-Martínez, Pedro; Corsolini, Simonetta (Toxics, 2025)
The aim of this study was to evaluate the concentration of polychlorinated biphenyls (PCBs) in chinstrap penguins (Pygoscelis antarctica) and krill (Euphausia superba) from Deception Island (South Shetland Islands, Antarctica) to provide additional data of the PCB presence in Antarctica. To this end, 34 samples of different tissues corresponding to four adult specimens and six chicks, and krill from the area were studied. The selected samples were analyzed for the determination of 27 congeners of PCBs by gas chromatography. Adult specimens accumulated PCBs mainly in the liver (33%, 1330.82 ± 733.69 pg·g−1 wet weight, w.w.) and muscle (25%, 1029.73 ± 823.4 pg·g−1 w.w.), whereas the brain showed the highest levels in chicks (36%, 1215.83 ± 955.19 pg·g−1 w.w.). Regarding krill, our results were five to eight times lower than the levels found in krill from King George Island and from the Ross Sea. Further, a distribution analysis of PCBs in penguins according to Regulation 2013/39/UE and Commission Regulation (EU) No 277/2012 was also performed, and PCBs were categorized into three groups (dioxin-like-mono-ortho, non-dioxin-like-indicators, and others-non-dioxin-like). The data indicate that the content of the other group was generally higher than that of the other two PCB groups for both adults and chicks. Notably, the liver consistently exhibited the highest proportion of the other group.